THE EFFECT OF TOTAL QUALITY MANAGEMENT (TQM) AND WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE (Study at Wood Processing Company in Lumajang Regency) - Fatimah, Iftah Nahdyatul; Putikadea, Insyirah (Jurnal Bina Bangsa Ekonomika, 2025)
This study analyzes the effect of total quality management (TQM) and work-life balance on employee performance. The methodology used is a questionnaire with 101 employee respondents working in a wood company in Lumajang Regency. The data was processed using multiple linear regression analysis to test the relationship between the research variables. The study's results indicate a positive effect of total quality management and work-life balance on employee performance.